PENGEMBANGAN MEDIA PAPAN BACA PINTAR BERBASIS LITERASI SAINS DI SDN 011 TARAKAN - Oktaviani, Dinda; Andari, Kadek Dewi Wahyuni; Bua, Agustinus Toding (Elementary School Teacher Education of STKIP Al Hikmah Surabaya, 2020)
Abstract  The aims of this research to develop learning media that can help students improve reading and writing skills. This research and development also helps teachers to make learning media easy and fun for students. The type of this research that is research and development. This research and development model refers to the Research and Development (R&D) stage proposed and modified by Borg and Gall. This research and development stage consists of nine stages: (1) potential and problems, (2) information gathering, (3) product design, (4) design validation, (5) design improvement, (6) product trials, (7) product revisions, (8) trial use, (9) product revisions. Data collection instruments used were, observation, interviews, validation sheets and student questionnaire responses. The results of smart reading board media research obtained from validation sheets and student questionnaire responses were said to be feasible. Based on the assessment conducted by media experts obtained an average score of 4 with a percentage of 95% and material experts with a percentage of 90%. Then the questionnaire responses of students in the trial use reached 100%. Based on the acquisition of the average score and percentage, the learning media of smart reading boards based on scientific literacy on the environment around my house, is said to be feasible to use.   Abstrak  Penelitian ini bertujuan mengembangkan media pembelajaran yang dapat membantu peserta didik dalam meningkatkan kemampuan membaca dan menulis. Penelitian dan pengembangan ini juga membantu guru untuk membuat media pembelajaran yang mudah dan menyenangkan bagi peserta didik. Jenis penelitian yang digunakan peneliti adalah penelitian dan pengembangan. Model penelitian dan pengembangan ini mengacu pada tahapan Research and Development (R&D) yang dikemukakan dan dimodifikasi oleh Borg and Gall. Tahapan penelitian dan pengembangan ini terdapat sembilan tahap, yaitu: : (1) potensi dan masalah, (2) pengumpulan informasi, (3) desain produk, (4) validasi desain, (5) perbaikan desain, (6) uji coba produk, (7) revisi produk, (8) uji coba pemakaian, (9) revisi produk. Instrumen pengumpulan data yang digunakan yaitu, observasi, wawancara, lembar validasi dan angket respon peserta didik. Hasil penelitian media papan baca pintar yang diperoleh dari lembar validasi dan angket respon peserta didik dikatakan layak. Berdasarkan penilaian yang dilakukan oleh ahli media memperoleh skor rata-rata 4 dengan persentase 95% dan ahli materi dengan persentase 90%. Kemudian angket respon peserta didik pada uji coba pemakaian mencapai 100%. Berdasarkan perolehan skor rata-rata dan persentase maka media pembelajaran papan baca pintar berbasis literasi sains pada materi lingkungan sekitar rumahku, dikatakan layak untuk digunakan.